The Effect of Leverage and Liquidity on Cash Dividend Policy with Profitability as Moderator Moderating - Nurchaqiqi, Rozi; Suryarini, Trisni (Universitas Negeri Semarang, 2018)
This study aims to determine the effect of leverage and liquidity on cash dividend policy with profitability as a moderating variable. The population of this study is 59 real estate, property and building construction companies which is listed in Indonesian Stock Exchange (IDX) during the year 2013-2015. Selection data of sample by using purposive sampling obtained sample of 23 companies and the unit analyze are 69. Data collection method used in this research is documentation. Methods of data analysis used descriptive statistical analysis and regression moderation with the test of absolute difference value. The results show that leverage and liquidity have positive significant effect on cash dividend policy. Profitability does not moderate the effect of leverage on cash dividend policy, but profitability can moderates the effect of liquidity on cash dividend policy. Based on the result of this study, it can be concluded that cash dividend policy is influenced by leverage and liquidity. Profitability does not moderate the effect of leverage on cash dividend policy but profitability can moderates the effect of liquidity on cash dividend policy.